2017
DOI: 10.1021/acs.jmedchem.7b00515
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Development of Covalent and Mutant-Selective Pyrazolopyrimidines to Target T790M Drug Resistance in Epidermal Growth Factor Receptor

Abstract: Reversible epidermal growth factor receptor (EGFR) inhibitors prompt a beneficial clinical response in non-small cell lung cancer patients who harbor activating mutations in EGFR. However, resistance mutations, particularly the gatekeeper mutation T790M, limit this efficacy. Here, we describe a structure-guided development of a series of covalent and mutant-selective EGFR inhibitors that effectively target the T790M mutant. The pyrazolopyrimidine-based core differs structurally from that of aminopyrimidine-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Further analysis of the physicochemical properties in vitro and in vivo demonstrated that 23 possessed the best overall profile, displaying a high kinetic solubility as well as an excellent permeability. 71 Maher et al designed a series of dual EGFR/ErbB2 inhibitors through the isosteric replacement of the quinazoline core of lapatinib and erlotinib, with a pyrazolo[3,4-d]pyrimidine core. The substitutions around this core primarily focussed on the incorporation of a library of substituted arenes in the C4-position linked by a variety of different nitrogen-containing moieties.…”
Section: Egfrmentioning
confidence: 99%
“…Further analysis of the physicochemical properties in vitro and in vivo demonstrated that 23 possessed the best overall profile, displaying a high kinetic solubility as well as an excellent permeability. 71 Maher et al designed a series of dual EGFR/ErbB2 inhibitors through the isosteric replacement of the quinazoline core of lapatinib and erlotinib, with a pyrazolo[3,4-d]pyrimidine core. The substitutions around this core primarily focussed on the incorporation of a library of substituted arenes in the C4-position linked by a variety of different nitrogen-containing moieties.…”
Section: Egfrmentioning
confidence: 99%
“…The coupling reaction proceeded smoothly with both unlabeled and labeled boronic acids using excess of reagents at room temperature. The crude product was deprotected with TFA in DCM and acylated with acryoyl chloride according to the known procedures 18–20 . 2.6 mg of [ 13 C 6 ]‐1 was then obtained by LC‐MS purification in 24% yield over three steps (10% yield based on the 21 and 7% based on [ 13 C 6 ]‐bromobenzene).…”
Section: Resultsmentioning
confidence: 99%
“…Our attempts started again with commercially available tert ‐butyl ( R )‐3‐(4‐amino‐3‐iodo‐1H‐pyrazolo[3,4‐d]pyrimidin‐1‐yl)piperidine‐1‐carboxylate 21 , which was converted into known hydroxyphenyl derivative 27 under Suzuki conditions (Scheme 7). 19 Purification by column chromatography provided the product in 72% yield.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were further screened against the third-generation EGFR inhibitor gefitinib and were found to be superior, concluding that the compounds synthesized were selective third-generation EGFR inhibitors. Further, 223 was taken up for preclinical study using the mice model and results showed good activity by the intraperitoneal route compared to that by intravenous ( Engel et al, 2017 ).…”
Section: Fused Pyrimidine Derivativesmentioning
confidence: 99%